Sosialisasi Pentingnya Informasi Saat Terdekteksi Covid 19 Dengan Konsntrasi Pada Pengelolaan Sumber Daya Manusi Ditaman Baca Perigi Sawangan Depok - Whina Ratnawati; Angga Pratama; Rahmi Andini S; Wahadi Siamto; Anisa Nurdina (Universitas Pamulang, 2022)
The implementation of Community Service (PKM) is one of the applications of the Tri Dharma of Higher Education which in its implementation makes a positive contribution to the community. The implementation of this PKM took the title